Low-level mosaic trisomy 21 at amniocentesis in a pregnancy associated with cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes, perinatal progressive decrease of the trisomy 21 cell line and a favorable fetal outcome - Chih-Ping Chen; Fang-Tzu Wu; Yen-Ting Pan; Peih-Shan Wu; Chen-Chi Lee; Chien-Ling Chiu; Wayseen Wang (Elsevier, 2024)
Objective: We present low-level mosaic trisomy 21 at amniocentesis in a pregnancy with a favorable fetal outcome. Case Report: A 38-year-old, gravida 2, para 1, woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 47,XY,+21[4]/46,XY[34]. Prenatal ultrasound findings were normal. At 27 weeks of gestation, she was referred for genetic counseling, and the cultured amniocytes had a karyotype of 47,XY,+21[2]/46,XY[26]. Quantitative fluorescent polymerase chain reaction (QF-PCR) analysis on the DNA extracted from uncultured amniocytes and parental bloods excluded uniparental disomy (UPD) 21. Interphase fluorescence in situ hybridization (FISH) analysis on uncultured amniocytes revealed 30% (30/100 cells) mosaicism for trisomy 21. Array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes revealed the result of arr 21q11.2q22.3 × 2.25, consistent with 20%-30% mosaicism for trisomy 21. The parental karyotypes were normal. The woman was advised to continue the pregnancy, and a 3510-g phenotypically normal male baby was delivered at 39 weeks of gestation. Cytogenetic analysis of the cord blood, umbilical cord and placenta revealed the karyotypes of 47,XY,+21[1]/46,XY[39], 47,XY,+21[2]/46,XY[38] and 46,XY in 40/40 cells, respectively. When follow-up at age 1 year and 2 months, the neonate was normal in phenotype and development. The peripheral blood had a karyotype of 46,XY in 40/40 cells, and interphase FISH analysis on uncultured buccal mucosal cells showed 6.4% (7/109 cells) mosaicism for trisomy 21. Conclusion: Low-level mosaic trisomy 21 at amniocentesis can be associated with cytogenetic discrepancy between cultured amniocytes and uncultured amniocytes, perinatal progressive decrease of the trisomy 21 cell line and a favorable fetal outcome.